Hubungan Asupan Zat Gizi Makro Pada Pekerja Dengan Obesitas Sentral Di Kecamatan Tenggarong - Sari, Rinten Anjang; Saqowati, Lika; Indah Mulyani, Rieska (Jurnal Kesehatan Mahardika, 2025)
Central obesity is a condition characterized by excess fat accumulation in the abdominal area, which increases the risk of degenerative diseases such as type 2 diabetes mellitus, cardiovascular disease, and cancer. This study aims to analyse the relationship between macronutrient intake, level of nutrition knowledge, and physical activity with the incidence of central obesity in workers at the Tenggarong District Office. This research used a cross-sectional design with a quantitative approach. The sample consisted of 35 workers selected through total sampling. Data on macronutrient intake were collected using a 24-hour food recall form for two non-consecutive days and analysed with Nutrisurvey 2007 software. Central obesity was assessed by measuring abdominal circumference using a metline according to the Indonesian Ministry of Health standards. The Spearman rank test was used for bivariate analysis. The results showed that the prevalence of central obesity among the workers was 85.7%. There was a significant relationship between energy intake (p=0.002), fat (p=0.001), carbohydrate (p=0.005), and physical activity (p=0.002) with central obesity. However, there was no association between protein intake (p=0.096) or level of nutrition knowledge (p=1.000) with central obesity. These findings indicate that dietary intake and physical activity play important roles in the incidence of central obesity among workers. Therefore, this study recommends implementing dietary changes and increasing physical activity as preventive measures to reduce or prevent central obesity in this population